Fear of Falls and Frailty: Cause or Consequence or Both? - Ray Marks (Journal of Aging Research And Healthcare, 2021)
Background Many older adults are vulnerable to becoming frail. They are also often at risk for falling and serious injuries and poor health outcomes. Aim This exploratory review examines the correlates of frailty, and fear of falling and their association insofar as older adults wellbeing may be jeopardized. Methods and Procedures Articles extracted from major electronic data bases that addressed the current topic of interest were used. Key findings regarding the syndromes of frailty and fear of falling were duly downloaded, analyzed and summarized in narrative form. Results A high proportion of older adults can be expected to exhibit frailty or become frail as they age. Many too are at risk for falls and fear of future falls, regardless of frailty status. A persistent fear of falls may however, heighten frailty risk or manifestations if not duly addressed in a timely manner. Conclusion Prompt comprehensive assessment of at risk older adults, as well as the frail and pre frail older adult, plus those who have fallen may avert serious injury and long term disability plus excess frailty and its deleterious impacts this syndrome has on aging older adults as well as societies.
Keywords: Aging